IT IS A WATER-SAVING TECHNOLOGY CREATED WITH THE POWERFUL SWELLING “HYDROGEL” - Sadullaev , Azamat Nafiddinovich; Ergashev , Mirsharif G‘anijon ugli (Educational Research in Universal Sciences, 2023)
Hydrogel is an artificial polymer that absorbs water, allowing it to retain moisture for a long time. Hydrogel, which is saturated with snow or rain or irrigation water, absorbs 250 to 400 times more water than its weight by slowly passing moisture to the roots of plants. Simply put, 10 gr. The polymer can hold between 2.4 and 4 liters of water. As for its efficiency, if used correctly, it will save 20 to 40% of irrigation water for most agricultural crops. It is well known that the water supply system is mainly divided into three systems: drinking and household water and industrial and agricultural water. It is necessary to clean the toilet before adding it to the water basins or the municipal sewage.